حقوق المرأة في قوانين الضمان الاجتماعي - محمد قرفي; سيف الدين عبدو (My University, 2018)
Summary Algerian legislation provides that social security is a right that benefits all sectors of society, including women's rights. With regard to the rights provided by the Algerian legislature to women under the social security laws, these rights are, in the course of their employment and because of their cessation of employment, the following rights are covered by the social security laws: Sickness insurance, childbirth insurance, work accident insurance, occupational disease insurance, invalidity insurance, death insurance, retirement insurance, unemployment insurance. Algerian legislator covered eight risks of social security coverage. Lastly, Algerian legislation had succeeded in acquainting itself with all the risks faced by women in their lives and had endeavoured to provide women with the necessary protection in social security laws. ............................ ملخص عمل المشرع الجزائري على أن يكون الضمان الاجتماعي حقا تستفيد منه كافة شرائح المجتمع، بما في ذلك المرأة وكذا ذوي حقوقها. أما بالنسبة للحقوق التي قدمها المشرع الجزائري للمرأة في ظل قوانين الضمان الاجتماعي، فتكون أثناء أدائها لعملها وكذا بسبب توقفها عن العمل، تتمثل هذه الحقوق في التأمين على المخاطر والتي شملتها قوانين الضمان الاجتماعي ألا وهي: التأمين على المرض، التأمين على الولادة، التأمين على حوادث العمل، التأمين على الأمراض المهنية، التأمين على العجز، التأمين على الوفاة، التأمين على التقاعد، التأمين على البطالة، فالمشرع الجزائري قد شمل ثمانية مخاطر بالتغطية في الضمان الاجتماعي. وما يمكن قوله في الأخير أن المشرع الجزائري قد نجح في الإلمام بكافة المخاطر التي تواجه المرأة في حياتها، وعمل على تقديم الحماية اللازمة للمرأة في قوانين الضمان الاجتماعي. ......................... Résume Le législateur algérien a travaillé, pour que l’assurance social soit un droit pour tous, aussi la femme et pour les droits que les législateurs a donné au femme algérienne telle que l'assurance social pendent son travail et aussi après sa cessation et bénéfice de s'assurance de danger qui à couvrir: L’assurance 'assurance des maladies, l’assurance des accidents du travail et les maladies professionnels, l'assurance d'incapacité, l'assurance de décès, l'assurance de retraite et chômage. Donc le législateur algérien couvre 08 dangers dans la couverture d’assurance sociale. Enfin, on peut dire que le législateurs algérien a réussi dans la couverture d’assurance sociale de tous les dangers qui menacent la femme, et à essayer de donner la sécurité nécessaire pour la femme dans les lois d’assurance social